Phenylindanes in Brewed Coffee Inhibit Amyloid-Beta and Tau Aggregation - Mancini, Ross S.; Wang, Yanfei; Weaver, Donald F. (Frontiers in Neuroscience, 2018)
Coffee consumption has been correlated with a decreased risk of developing Alzheimer’s disease (AD) and Parkinson’s disease (PD), but the mechanism by which coffee may provide neuroprotection in humans is not fully understood. We hypothesized that compounds found in brewed coffee may elicit neuroprotective effects by inhibiting the aggregation of amyloid-beta (Aβ) and tau (AD) or α-synuclein (PD). Three instant coffee extracts (light roast, dark roast, decaffeinated dark roast) and six coffee components (caffeine (1), chlorogenic acid (2), quinic acid (3), caffeic acid (4), quercetin (5) and phenylindane (6)) were investigated for their ability to inhibit the fibrillization of Aβ and tau proteins using thioflavin T (ThT) and thioflavin S (ThS) fluorescence assays, respectively. Inhibition of Aβ and α-synuclein oligomerization was assessed using ELISA assays. All instant coffee extracts inhibit fibrillization of Aβ and tau, and promote α-synuclein oligomerization at concentrations above 100 μg/mL. Dark roast coffee extracts are more potent inhibitors of Aβ oligomerization (IC50 ca. 10 μg/mL) than light roast coffee extract (IC50 = 38.9 μg/mL), and pure caffeine (1) has no effect on Aβ, tau or α-synuclein aggregation. Coffee components 2, 4 and 5 inhibit the fibrillization of Aβ at 100 μM concentration, yet only 5 inhibits Aβ oligomerization (IC50 = 10.0 μM). 1–5 have no effect on tau fibrillization. Coffee component 6, however, is a potent inhibitor of both Aβ and tau fibrillization, and also inhibits Aβ oligomerization (IC50 = 41.8 μM). Coffee components 4 and 5 promote the aggregation of α-synuclein at concentrations above 100 μM; no other coffee components affect α-synuclein oligomerization. While the neuroprotective effect of coffee consumption is likely due to a combination of factors, our data suggest that inhibition Aβ and tau aggregation by phenylindane 6 (formed during the roasting of coffee beans, higher quantities found in dark roast coffees) is a plausible mechanism by which coffee may provide neuroprotection. The identification of 6 as a dual-inhibitor of both Aβ and tau aggregation is noteworthy, and to our knowledge this is the first report of the aggregation inhibition activity of 6.